2018
DOI: 10.1088/1361-6595/aacf32
|View full text |Cite
|
Sign up to set email alerts
|

Transient voltage analysis on a series capacitor of the floating probe for plasma diagnostics

Abstract: An electrical plasma diagnostic method is proposed to determine plasma density and electron temperature. When two square voltages with different amplitudes are applied to a probe tip, a capacitor connected to the probe is charged due to the current flowing from the plasma. To obtain the plasma parameters, a circuit model with a nonlinear sheath and capacitor is proposed. The electron temperature and plasma density given by the model can be obtained from the ratio of the capacitor voltages. The results are in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Among these methods is the floating probe method, in which an ac voltage is applied to the probe via a blocking capacitor. This method has been studied by Braithwite et al [12] and Lee et al [13], among others [14], [15], [16]. Another method, known as the pulsed probe method [17], [18], uses a pulse signal for probe measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods is the floating probe method, in which an ac voltage is applied to the probe via a blocking capacitor. This method has been studied by Braithwite et al [12] and Lee et al [13], among others [14], [15], [16]. Another method, known as the pulsed probe method [17], [18], uses a pulse signal for probe measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al measured the electron temperature using the floating potential difference by applying AC voltage to the probe tip and the ion density using the first harmonic current [7]. In recent work, we suggested the method of applying the square voltages to the probe tip and analysed the transient voltage of the capacitor connected in series to the probe for obtaining the electron temperature and ion density [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method cannot be used in processes where the exposed probe tip is coated with the dielectric lm. To overcome this limitation, electrical diagnostic methods have been suggested that use AC voltages applied to the probe [13][14][15][16][17]. Lee et al proposed the oating harmonic method (FHM), in which a sinusoidal voltage with a frequency in the range of kHz is applied to a probe [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al used the self-bias effect by applying sinusoidal voltages to a probe because the change in oating potential is related to electron temperature [14]. Our previous study proposed an electrical diagnostic method applying square voltages because the transient voltage of a series capacitor connected to the oating probe is a function of plasma density and electron temperature [17].…”
Section: Introductionmentioning
confidence: 99%